IMPROVEMENT OF DRUG FORM PREPARATION TECHNOLOGY FROM DRY EXTRACT OF MEDICINAL PLANTS FOR DIGESTIVE SYSTEM WOUND DISEASES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This study explores advanced pharmaceutical technologies for developing drug formulations using dry extracts from medicinal plants, aimed at healing digestive tract injuries. It examines innovative extraction methods, formulation optimization, and improved delivery systems to enhance bioavailability and therapeutic effects. Techniques like spray-drying, freeze-drying, and supercritical fluid extraction are employed to standardize active compounds while preserving biological activity. The findings show improved drug stability, dissolution, and targeted delivery, supported by advanced analytical methods. The research supports the creation of modern, evidence-based phytopharmaceuticals that align with regulatory standards while maintaining traditional efficacy.